2009
DOI: 10.1016/j.otohns.2008.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Hemostasis during functional endoscopic sinus surgery: The effect of local infiltration with adrenaline

Abstract: Topical use of adrenaline achieved similar hemostatic effect compared with injection of adrenaline. Intranasal injection of a vasoconstrictor, in consideration of its adverse effects, may be avoided during surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
1
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 19 publications
3
38
1
7
Order By: Relevance
“…It has also been reported that acceptable dose of adrenaline may induce cardiac pathology in a patient with no history of coroner artery disease [8]. In addition sometimes cardiologic disorders may not be detected by electrocardiogram or another routine tests [1]. Cardiac arrhythmia is the most seen side effect according to our experience.…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…It has also been reported that acceptable dose of adrenaline may induce cardiac pathology in a patient with no history of coroner artery disease [8]. In addition sometimes cardiologic disorders may not be detected by electrocardiogram or another routine tests [1]. Cardiac arrhythmia is the most seen side effect according to our experience.…”
Section: Discussionsupporting
confidence: 54%
“…Good visualization is actually critical because the smaller anatomical structure in addition to vascularity in the nose limits access of vision and in many cases a small hemorrhage may reduce completeness in the surgical procedure. Septoplasty surgeon usually use an intranasal injection of the vasoconstrictor to enhance the operative area in the course of septal surgery [1].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations